Perception And Practices of Healthy Lifestyle in Late Adolescence and Its Impact on Body Mass Index - Hala M Elsabagh; Fatma E Soliman; Lulah A Hassan (Medsci Publications, 2016)
Background: Adolescence coincides with major changes that affect the determinants of adult health. Many adult health conditions are related to factors that develop during adolescence. Aim: This study aimed to investigate the impact of dietary habits and physical activity on BMI of late adolescent college students. Methodology: Cross sectional study was conducted in the first three years of medical and nursing students, Tanta University. A self-administered questionnaire was used. It included questions on socio-demographic, dietary habit, physical activity and perception of healthy lifestyle. Results: Out of 524 students 55.5% were rural residents and 67.9% were females and 31.3% were having overweight. Drinking soda /sugared beverages (juices) is significantly high in obese students. More than half (53.1%) of OB students and (44.5%) of OW students usually eat snacks between meals. Physical activity is low among studied students, 45% of them did not have routine exercise. Obese and overweight students had negative attitude towards healthy lifestyle. Lack of time is the main barrier to adopt healthy lifestyle. Conclusion: Fault dietary habits, lack of physical activity and high sedentary practice affect the BMI. Negative perception of healthy lifestyle and lack of time constitute the main barriers against healthy lifestyle.